THE CRISIS OF THE FARMING IN STAVROPOL REGION IN THE EARLY XXth CENTURY AND THE PROBLEM OF THE INTENSIFICATION OF THE AGRARIAN SECTOR - Viktor Ermakov; Tatyana Mamedova (Гуманитарные и юридические исследования)
The given material examines the prospects of the development of the farming in Stavropol region in the early 20th century. The authors come to the conclusion that under the conditions of the demographic boom and the extensive forms of farming inherent in peasants the land problem in the region was becoming acute. This factor led to the rise in the land rent in the region.